Surufatinib related nephrotic syndrome in a pancreatic neuroendocrine tumor: a case report and review of literature - Shi, Chengqian; Lin, Jinglian; Xiang, Xiadan; Bao, Wenlong; Yang, Jie (Frontiers in Oncology, 2025)
Pancreatic neuroendocrine tumors (pNETs) are rare, heterogenous neoplasms originating from pancreatic neuroendocrine cells, which regulate hormone secretion and metabolic homeostasis. Surgery is the primary method of control and potential cure for pNETs and targeted therapies have also been investigated for low-grade inoperable or distant metastatic pNETs. Surufatinib, an oral angio-immuno kinase inhibitor, is approved for treating inoperable or late-stage, low-grade (G1 and G2), well-differentiated pNETs and extrapancreatic neuroendocrine tumors. This study describes a case of nephrotic syndrome in a middle-aged woman with pNETs. This patient showed nephrotic syndrome after surufatinib treatment 3 months and renal pathology suggested IgA nephropathy with moderate podocyte injury. However, the nephrotic syndrome was relieved after 2 weeks of discontinuation of surufatinib. After resuming treatment with low-dose surufatinib for 2 weeks, the random proteinuria quantification was increased and the proteinuria turned negative after discontinuation of surufatinib again. It provides a reference for surufatinib related nephrotic syndrome in patients with pNETs and the potential mechanism between surufatinib and podocyte injury in IgA nephropathy needs to be investigated.